The Glocal World of Historical Archives: Editorial (Glocalism: Journal of Culture, Politics and Innovation, 2021)
In 2021, we commemorate 500 years since the fall of the Aztec capital Tenochtitlan and the subsequent foundation of Mexico City by the Spanish. That event had a huge impact on world history, not only in terms of redefining Atlantic connections but also by setting in motion a complex series of glocalization processes. In this editorial that introduces a monographic issue on the “glocal world of historical archives”, we take a cue from that event in our effort to analyze the underground networks and the sometimes-mysterious intertwining that connect apparently distant documentary sources. We propose that the historical experience and the practical use of archives are not minor problems in a glocal approach: thinking about the glocal (and changing) complexity of archives as the core theme of historical research. This concerns all hermeneutic and holistic views of social investigation that must discuss the configuration of archives as another crucial element of the contemporary age, in search of the secret connections between past, present, and future.
Keywords: historical archives; colonial archive; glocal world; documents; Tenochtitlan